PROTECTIVE COVERINGS FOR ICE AND SNOW - AQUEOUS FOAM STUDIES - Stehle, N. S. (1964)
Summer deterioration of their surfaces hampers the year-round use of natural ice islands and smooth sea-ice areas in the Arctic Ocean and permanent snow and ice areas in the antarctic. Sawduct has been used by the Navy for protecting compacted-snow areas, but its scarcity and shipping bulk preclude its use in polar regions. In developing a suitable protective covering for ice and snow surfaces in polar regions, laboratory and field studies were conducted on protein-base aqueous foams stabilized with sodium carboxymethyl cellulose. These foams are not adequate for continued protection of ice and snow surfaces against summer deterioration. They are difficult to generate, will not cure under normal polar conditions, have a short field life, are damaged by traffic, and offer only a slight weight saving over sawdust at a considerable increase in cost. Investigations should continue toward developing a covering for operational areas of ice and snow which protects against deterioration from solar radiation and near-thawing temperatures.